Análisis del uso de políticas, estrategias y recursos comunicacionales que utiliza la asociación artesanal Divino Niño del barrio Cera, parroquia Taquil, cantón Loja y su influencia en la imagen organizacional y desarrollo comercial. segundo semestre de 2013. Propuesta alternativa - Torres Jiménez, Eugenia Maricela (2015)
This work is based on the theme: Analysis of the use of policies, strategies and communication resources used by the Artisan Association "Divine Child", which aims to create a communication plan. The organization is located in the Province of Loja, in Taquil, Barrio Wax Parish. It is one of the areas with the greatest development in wax-based products, 80% of locals are engaged in that activity. It should be noted that artisans promote the conservation of their culture and tradition, however lack of communication strategies that have limited growth in the commercial sector. The study area has a cultural potential, it can become a place with adequate visual image through communication mechanisms that contribute to position your brand, for that reason this research work, which aims to create it posed a communication plan to promote handicrafts as a new alternative. Currently the association lacks communication tools, witnessing at first sight that has neither a sign with which the organization can locate in the neighborhood, because its distribution was limited both by the partner and the means of communication. From this perspective was implemented as a general purpose "analyze the use of policies, strategies and communication resources", reciprocating the same plated Specific objectives: identify problems of organizational communication; investigate causes and effects of lack of communication strategies and their impact on productive activities; and propose the implementation of communication strategies to improve the marketing of their products through their image. Among the methods used is deductive and inductive to know the reality of the problem of study, plus the comparative and statistical methods applied to the information obtained. Together and work for the development of techniques of observation, interviews and surveys were used. With regard to the conclusions may be mentioned that the association does not have a communication plan. It was also concluded that for the promotion and positioning is necessary to create a visual plan. Finally the paper concludes with socialization among members and tesista for the implementation of the proposal and sustainable development is given.